Ricin!: the inside story of the terror plot that never was - Archer, Lawrence (Pluto Press, 2010)
In January 2003, the British media splashed the news that anti-terror police had disrupted an Al-Qaeda cell, poised to unleash the deadly poison ricin on the capital. Police had reportedly found traces of ricin, as well as a panoply of bomb and poison-making equipment in the cell's 'factory of death' - a shabby flat in north London. But when the 'ricin plot' came to trial at the Old Bailey, a very different story emerged: there was no ricin and no plot. For the first time, this book tells the inside story of what really happened